2008
DOI: 10.1080/09638180802016627
|View full text |Cite
|
Sign up to set email alerts
|

Experienced and Novice Investors: Does Environmental Information Influence Investment Allocation Decisions?

Abstract: This paper examines the effect of environmental information on investment decisions. The results are based on an experiment in which groups of investors (varied by experience) were asked to make short- and long-term investment allocation decisions based on financial information and on supplementary environmental information (varied between cases). The results suggest that environmental information disclosure influences investment allocation decisions. The results also suggest that potentially mitigating factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 53 publications
8
69
0
4
Order By: Relevance
“…In addition, Rikhardsson and Holm (2008) find that adding quantitative ESG information mitigates rather than extends the directional effect of qualitative ESG information. In a second experiment, Holm and Rikhardsson (2008) again find support for the notion that ESG reporting influences investment-allocation decisions. However, they extend prior research by analysing moderating factors such as the experience level of investors which affect the observed investment allocation decisions.…”
Section: The Example Of Esg Reportingmentioning
confidence: 64%
“…In addition, Rikhardsson and Holm (2008) find that adding quantitative ESG information mitigates rather than extends the directional effect of qualitative ESG information. In a second experiment, Holm and Rikhardsson (2008) again find support for the notion that ESG reporting influences investment-allocation decisions. However, they extend prior research by analysing moderating factors such as the experience level of investors which affect the observed investment allocation decisions.…”
Section: The Example Of Esg Reportingmentioning
confidence: 64%
“…Essa característica faz com que decisores usualmente não sejam hábeis em tomar decisões plenamente racionais no tocante a investimentos desse tipo. Diversos aspectos podem influenciar suas decisões, tais como ancoragem em experiências anteriores, crenças, informações incompletas, pouca racionalidade, entre outros (Bannister & Remenyi, 2000;Clemons & Weber, 1990;Holm & Rikhardsson, 2008;Renkema, 1998;Sanchez & Albertin, 2009). Esses aspectos podem trazer grandes dificuldades para os gestores avaliarem adequadamente os aportes de recursos sobre a infraestrutura necessária para operacionalização dos sistemas de informação, uma vez que estes aportes podem gerar benefícios indiretos e intangíveis (Clemons & Weber, 1990;Davern & Kauffman, 2000;Ryan & Harrison, 2000).…”
Section: H1unclassified
“…Holm & Rikhardsson [26,27] found that environmental information has the potential to affect investment decisions-although this is affected by the investment time scale, the experience of the investor, and whether the information provided is qualitative or quantitative. However, Koellner et al [28] suggested that there is a need for a reliable comparative assessment of sustainability of ethical funds, which is not currently available, to support investment choices.…”
Section: Literature Reviewmentioning
confidence: 99%